1996
DOI: 10.1152/ajpheart.1996.271.5.h2145
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of postischemic reperfusion injury is related to prevention of [Ca2+]m overload in rat hearts

Abstract: Intracellular calcium overload has been implicated in postischemic reperfusion injury. In myocytes, mitochondrial free calcium concentration ([Ca2+]m), not cytosolic free calcium concentration ([Ca2+]c), overload is related to reoxygenation injury. We tested the hypothesis that [Ca2+]m, not [Ca2+]c, overload is an important mediator of reperfusion injury in whole hearts. [Ca2+]m and [Ca2+]c were assessed using indo 1 fluorescence in isolated rat hearts subjected to 45 min of ischemia and 20 min of reperfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 0 publications
11
123
1
1
Order By: Relevance
“…It has been reported that uncoupling of oxidative phosphorylation in cardiac mitochondria by the classical uncoupling agent dinitrophenol also protects postischaemic cardiac function, which supports the concept that stressful, stimuli to the mitochondrion may result in cardioprotection, in the same way as ischaemic preconditioning (Minners et al 2000). Furthermore, both pinacidil and diazoxide have been shown to uncouple cardiac mitochondria (Garlid 1996;Miyamae et al 1996;Garlid et al 1997;Holmuhamedov et al 1998). The observed preservation of postischaemic cardiac function was similar for pinacidil and diazoxide in the present study.…”
Section: Haemodynamic Effectssupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that uncoupling of oxidative phosphorylation in cardiac mitochondria by the classical uncoupling agent dinitrophenol also protects postischaemic cardiac function, which supports the concept that stressful, stimuli to the mitochondrion may result in cardioprotection, in the same way as ischaemic preconditioning (Minners et al 2000). Furthermore, both pinacidil and diazoxide have been shown to uncouple cardiac mitochondria (Garlid 1996;Miyamae et al 1996;Garlid et al 1997;Holmuhamedov et al 1998). The observed preservation of postischaemic cardiac function was similar for pinacidil and diazoxide in the present study.…”
Section: Haemodynamic Effectssupporting
confidence: 89%
“…In this way, it will be protective for postischaemic cardiac function (D'Alonzo et al 1994). For diazoxide and also for pinacidil, this can be explained by the specific opening of mitochondrial K ATP channels (Miyamae et al 1996;Garlid et al 1997;Holmuhamedov et al 1998). Until now, no consensus has been reached on how exactly this opening of mitochondrial K ATP channels results in protection of postischaemic cardiac function.…”
Section: Haemodynamic Effectsmentioning
confidence: 99%
“…We have reported 10 plays a pivotal regulatory role linking cardiac mechanics and energy production. 37,38 Inhibiting mitochondrial Ca 2ϩ uptake was shown to attenuate mechanical dysfunction after warm ischemia and reperfusion without altering cytosolic [Ca 2ϩ ]. 37 Hypothermia helps to preserve mitochondrial function during subsequent ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Inhibiting mitochondrial Ca 2ϩ uptake was shown to attenuate mechanical dysfunction after warm ischemia and reperfusion without altering cytosolic [Ca 2ϩ ]. 37 Hypothermia helps to preserve mitochondrial function during subsequent ischemia. 39 Hypothermia-induced changes in Na ϩ , Ca 2ϩ , K ϩ , and H ϩ homeostasis largely protect the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The MCU is therefore a prime target as drugs that inhibit this Ca 2þ uptake system should retain the beneficial effects conferred by PTP inhibition but not its adverse effects. Accordingly, inhibition of the MCU by ruthenium red protects hearts against ischemia injury [125]. Unfortunately ruthenium red is a very unspecific inhibitor that also inhibit several classes of ion channels and that interfere with the binding of Ca 2þ to calmodulin (reviewed in [26]).…”
Section: Therapeutic Strategies To Protect Neurons During Ischemia Bymentioning
confidence: 99%